Pembelajaran Berbasis Praktik dalam Pedagogi Musik Instrumental: Hambatan Integrasi Akademik-Profesional dan Kerangka Konseptual Integratif - Sena Radya Iswara Samino; Tomy Agung Sugito; Dedy Setyawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The misalignment between academic orientation and professional practice demands in instrumental music education indicates a gap in the integration of graduate competencies. The relevance of learning is influenced by formal curricular structures that tend to be rigid, resulting in inconsistent connections with professional practice. This study employs a qualitative approach using a narrative literature review design with thematic synthesis. The data corpus consists of 25 scholarly articles published between 2019 and 2026, sourced from Google Scholar, Scopus, SINTA, and Garuda. The analysis identifies structural barriers, including curricular fragmentation and limited connectivity with professional ecosystems. The dominance of product-oriented assessment constrains the development of learning processes, while limited digital infrastructure weakens the integration between academic learning and real-world practice. An Integrative Conceptual Framework (ICF) is proposed as an analytical tool to interpret and guide the development of instrumental music pedagogy. The framework comprises epistemological foundations, adaptive curricular design, and institutional ecosystem connectivity. Strengthening the relationship between educational institutions and industry is essential for the effective implementation of this framework.